The Influence of Brand Image, Healthy Lifestyle, and Product Quality on The Purchase Decision of Antis Handsanitizer in South Jakarta - Jessica; Elwisam; Digdowiseiso , Kumba (CV ODIS, 2023)
This research is the result of research on the Influence of Brand Image, Healthy Lifestyle, and Product Quality on the Purchase Decision of Antis Hand Sanitizer in South Jakarta. The research method used is quantitative. The analysis method uses descriptive analysis and inferential analysis. Data analysis of several tests, namely instrument tests, classical assumption tests, model feasibility tests, multiple liner analysis, and t hypothesis testing, the subject of this study is the buyer of Antis Hand Sanitizer with a data collection method through questionnaires. Primary data was obtained through the distribution of questionnaires and processed with SPSS 23 tools. The results of regression analysis in this study show a positive and significant influence on purchasing decisions, which is shown in the coefficient table in the regression equation model. The results of the model feasibility test are shown with significant values that mean the model in this study is feasible to use based on the significant value obtained. The results of the conclusion of the hypothesis with the t-test obtained significant values on brand image variables, healthy lifestyle variables, and product quality variables. So it can be stated that the three independent variables have a significant influence on the dependent variable, namely the purchase decision.